Le « paysage de l’historien » : entre sources et méthodes - Marie Delcourte (Projets de Paysage)
The notion of the landscape is polysemic, making an interdisciplinary approach possible. It has become a transverse notion introducing new scientific practises. Analysing the structural elements of the landscape is equivalent to analysing “hybrid objects” which cannot be approached from the sole perspective of the natural sciences. This article attempts to explain how an historian considers the landscape (concepts, tools and methods) through the example of the dynamics of the woodlands in the Avesnois region in the North of France.